Interferon Regulatory Factors 1 and 2 Play Different Roles in MHC II Expression Mediated by CIITA in Grass Carp, Ctenopharyngodon idella - Lu, Xiao-Bing; Wang, Zhao-Xi; Liu, Shu-Bo; Zhang, Xiang-Yang; Lu, Long-Feng; Li, Shun; Chen, Dan-Dan; Nie, Pin; Zhang, Yong-An (Frontiers in Immunology, 2019)
Expression of major histocompatibility complex class II (MHC II) molecules, which determines both the immune repertoire during development and subsequent triggering of immune responses, is always under the control of a unique (MHC class II) transactivator, CIITA. The IFN-γ-inducible MHC II expression has been extensively and thoroughly studied in humans, but not in bony fish. In this study, the characterization of CIITA was identified and its functional domains were analyzed in grass carp. The absence of GAS and E-box in the promoter region of grass carp CIITA, might imply that the cooperative interaction between STAT1 and USF1 to active the CIITA expression, found in mammals, is not present in bony fish. After the transfection of IFN-γ or IFN-γ rel, only IFN-γ could induce MHC II expression mediated by CIITA. Moreover, interferon regulatory factor (IRF) 2, which cooperates with IRF1 to active the CIITA promoter IV expression in mammals, played an antagonistic role to IRF1 in the activation of grass carp CIITA. These data suggested that grass carp, compared with mammals, has both conservative and unique mechanisms in the regulation of MHC II expression.